2018
DOI: 10.1139/bcb-2018-0117
|View full text |Cite
|
Sign up to set email alerts
|

Human adenoviral DNA association with nucleosomes containing histone variant H3.3 during the early phase of infection is not dependent on viral transcription or replication

Abstract: Adenovirus (Ad) DNA undergoes dynamic changes in protein association as the virus progresses through its replicative cycle. Within the virion, the Ad DNA associates primarily with the virus-encoded, protamine-like protein VII. During the early phase of infection (∼6 h), the viral DNA showed declining association with VII, suggesting that VII was removed from at least some regions of the viral DNA. Within 6 h, the viral DNA was wrapped into a repeating nucleosome-like array containing the histone variant H3.3. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 69 publications
3
30
0
Order By: Relevance
“…A preliminary study assessing hexon, penton, and fiber protein levels from the capsids of cell surface-attached and internalized virions indicated that the drug does not adversely affect virus attachment (data not shown), which is consistent with studies reporting that HDAC inhibitors do not downregulate cell surface expression of the coxsackie adenovirus receptor (39). HAdV DNA associates with nucleosomes soon after reaching the host cell nucleus (29,30), so we next examined the impact of SAHA on Ad-late/RFP genome "chromatinization" by using a chromatin immunoprecipitation (ChIP) assay at 6 h following infection and drug treatment. Consistent with previous studies (29,30), we found that the early E1A region associated with H3 ( Fig.…”
supporting
confidence: 82%
See 3 more Smart Citations
“…A preliminary study assessing hexon, penton, and fiber protein levels from the capsids of cell surface-attached and internalized virions indicated that the drug does not adversely affect virus attachment (data not shown), which is consistent with studies reporting that HDAC inhibitors do not downregulate cell surface expression of the coxsackie adenovirus receptor (39). HAdV DNA associates with nucleosomes soon after reaching the host cell nucleus (29,30), so we next examined the impact of SAHA on Ad-late/RFP genome "chromatinization" by using a chromatin immunoprecipitation (ChIP) assay at 6 h following infection and drug treatment. Consistent with previous studies (29,30), we found that the early E1A region associated with H3 ( Fig.…”
supporting
confidence: 82%
“…During infection, the pVII-wrapped viral DNA enters the host cell nuclei through the nuclear pores (28). In the early phase of infection, the HAdV DNA dissociates from pVII, associates with cellular proteins, including histones, and adopts a nucleoprotein structure similar to the host DNA (29,30). The nucleosome density on the viral DNA is significantly reduced during late infection, and at least some of the newly synthesized viral DNA must associate with pre-pVII for packaging into newly formed capsids (30)(31)(32).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…While it is likely that the modification of viral chromatin influences viral DNA replication, how the presence of cellular histones on viral DNA may influence this process is unknown. Although cellular histones may be present on both incoming and de novo viral genomes , it is unclear whether these histones are removed by the process of replication, or indeed whether they must be removed or temporarily displaced for replication to take place. What is clear is that encapsidated viral genomes are devoid of cellular histones .…”
Section: Viral Chromatin and The Recruitment Of Nucleolar Proteinsmentioning
confidence: 99%